1993
DOI: 10.1023/a:1018926215306
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Solvent flow generated during iontophoresis can be used to convect neutral molecules through the skin, thereby greatly enhancing their flux. This concept was exploited to realize noninvasive glucose measurement by its iontophoretic extraction from the subcutaneous tissue. The hypothesis was tested in vitro using hairless mouse skin. The dermal surface was bathed with a glucose solution; chambers on the epidermal surface housed the current delivery electrodes. Iontophoresis (at 0.36 mA/cm2) was performed for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…It can be seen that, as had been predicted, the current responses of the biosensors all had increase relative to the backgrounds no matter the counter electrode of the biosensor served as anode or cathode, and the increment serving as cathode relative to the background current was significantly greater than that as anode on the same condition. The latter is attributed to the property of the skin, which has net negative charge at physiological condition making the neutral molecules induce positive charge on the periphery and moving preferentially from anode to cathode [6]. These results are consistent with the conclusions arrived at by liquid scintillation counting [4,7,8] or high-performance liquid chromatography [27], and more important, they testify the feasibility and validity of the amperometric approach adopted in this paper.…”
Section: In Vitro Measurements Of Electroosmotically Extracted Glucosesupporting
confidence: 88%
“…It can be seen that, as had been predicted, the current responses of the biosensors all had increase relative to the backgrounds no matter the counter electrode of the biosensor served as anode or cathode, and the increment serving as cathode relative to the background current was significantly greater than that as anode on the same condition. The latter is attributed to the property of the skin, which has net negative charge at physiological condition making the neutral molecules induce positive charge on the periphery and moving preferentially from anode to cathode [6]. These results are consistent with the conclusions arrived at by liquid scintillation counting [4,7,8] or high-performance liquid chromatography [27], and more important, they testify the feasibility and validity of the amperometric approach adopted in this paper.…”
Section: In Vitro Measurements Of Electroosmotically Extracted Glucosesupporting
confidence: 88%
“…He founded Cygnus Inc. and in addition to the development of passive transdermal systems, the company was the leader in developing reverse iontophoresis for noninvasive therapeutic monitoring - in particular, the Glucowatch to measure blood glucose levels. The technique had been developed in Richard Guy's laboratory at the University of California - San Francisco [52] and he collaborated closely with Russell Potts (who was VP for research at Cygnus Inc.; fig. 3e) [53].…”
Section: Epiloguementioning
confidence: 99%
“…The missing part that normally might be ignored was found and the rest is history...' That is how glucose sampling started, an observation which would lead to the Glucowatch Biographer™ and opened the field of reverse iontophoresis. Proof of concept experiments were described in the papers by Rao et al [22,63] who identified key issues as the glucose skin reservoir, measurement artefacts, and looked into the feasibility and reproducibility of the technique. A patent was filed [64], the technology developed by the team led by Potts at Cygnus and the Glucowatch Biographer approved by the Food and Drug Administration in 2001.…”
Section: Iontophoresismentioning
confidence: 99%